Development of Adolescent Reproductive Health Module Media - Siti Rofi'ah; Sri Widatiningsih (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2021)
Reproductive health received special attention globally at the 1994 International Conference on Population and Development (ICPD) in Cairo, Egypt. Since the conference, the rights of youth to be well informed about reproductive health and reproductive health services have been consistently confirmed. One of the efforts to fulfill these rights is by providing knowledge using health education media, including a module. To develop a product in form of a module which contains information on adolescent reproductive health as an innovative effort that are acceptable in terms of feasibility. This development research uses quantitative and qualitative methods, applying the Borg Gall development model which has been modified by the Center for Education Policy and Innovation Research Team of the Research and Development Agency of the Ministry of National Education. In order to determine the feasibility of the module, the product validity test was carried out by material experts, media experts, practitioner experts, and module trials. A questionnaire was used as the instrument to determine the feasibility of the module. A health education media has been produced in the form of a module that has been validated by 3 (three) experts, namely health promotion experts, health promotion practitioners and media experts and has been declared feasible and has been tested on a small group of 30 teenagers. The module has been declared eligible and has an ISBN and has had a creation record. It is recommended that the Health Promotion team of the public health cooperate with the BKKBN to educate peer counselors and use the module in providing health education about adolescent reproductive health